Sistem Abensi Karyawan Berbasis Location Based Services (LBS) Menggunakan Platform Android Studi Kasus: PT.Noxus Ideata Prima - Annisa Dayumi; Muhamad Femy Mulya (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2018)
Abstract— As a company, PT. Noxus Ideata Prima is highly dependent on its human resources, as they are the main gear which moves the company. Based on said fact, employee scoring procedures are needed by the company to assess perfomances of each employee. one of considered factors which affect an employee’s perfomancesis attendance. Based on above statement, this research is conducted in order to increase effectivity and efficiency, and also modernizing the currently active manual employee attendance system to become an Android-based mobile application with Location Based System (LBS). The development of this system utilizes System Development Life Cycle (SDLC) method with waterfall model and developed in C# programming language, which also utilizes other important elements, including XML, JSON Data, RESTful API, and PostgreSQL. There are several main functions and features offered by the application, including attendance function for the employee to use after coming to the office, holiday-checking for the current year, and viewing reports of attendance of each employee which can be seen monthly, yearly, or as the data from previous year. Keyword: Attendance, Mobile Android, (Location Based System), C#